SYSTEMATIC LITERATURE REVIEW: DESAIN PEMBELAJARAN LITERASI NUMERASI BERBASIS ESD UNTUK SISWA SD - Sari Rahayu; Santi Farida Syahrul; M. Zainal Arifin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The literacy numeracy skills of Indonesian students are still lagging compared to other countries. This can be due to various factors, including the lack of exploration of literacy numeracy learning design based on sustainable education (ESD) in the learning process. This study aims to describe how the design of literacy numeracy learning based on Education for Sustainable Development (ESD) works and develops in schools. The research method used is Systematic Literature Review (SLR), where the data obtained is by documenting articles that have been searched in the Google Scholar through PoP and then analyzing the results. The results of the study showed that the design of literacy numeracy learning based on ESD can improve the literacy numeracy skills of students. However, there are several inhibiting or hindering factors experienced in the implementation processes, such as the limited ability of the teachers to create HOTS questions, the absence of the literacy numeracy program from schools, and the lack of opportunities for students to study literacy numeracy in more depth. Therefore, the design of literacy numeracy learning based on ESD needs to be further developed, especially in terms of integrating literacy numeracy topics with sustainable education, developing learning models that are appropriate for the stages of student development, and developing more innovative and interesting learning media.